Muhammad Ibn Abdul Wahab 1703-1791 (Sejarah dan Perjuangannya) - Syamsuez Salihima (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2009)
Wahabi is a religious movement/organization established by Muhammad lbn-'Abd Al- Wahhab, (1703-1791). The term Wahabi is attributed to his name. The main teaching of this organization is Tauhid. According to him, tauhid constitutes the nucleus doctrine of Islamic teaching. The unity of God is revealed in the three forms. First: Tauhid al-Rububiyah. explaining the unity of God and His action. God is creator, preserver and decider of this universe. Second: Tauhid al Asma' wa al-Sifat (the unity of name and atributes). relates to God's attributes. He is the owner of anything in this universe. Third; Tauhid al-Ilahiyyah; explaining that He is the only God absolutely worshipped. There is no God but Him and Muhammad is His messenger. It means that all worships is just for Him. Muhammad is not worshipped but obeyed and followed.